Contrato de sociedade e críticas à affectio societatis - Mimica, Rafael Medeiros (2023)
The purpose of this dissertation is to confirm that affectio societatis, a Latin expression whose origin goes back to Roman law, does not correspond to a constitutive element of the partnership agreement. As a matter of fact, even today, affectio societatis does not have a clear and precise definition. For some, it corresponds to a willingness, a consent to take part in partnership, what suggests an extremely subjective trait. For others, the expression refers to the active collaboration that the partners undertake when entering in a partnership agreement. Although affectio societatis was important at a given moment in history, today it does not, or should not, have greater relevance. However, still today part of the doctrine understands it as essential to the existence of a partnership agreement, as well as that its disappearance allows the dissolution of social ties. That does not seem right to us. First, because there is only a partnership agreement when an organization marked by a high degree of institutionalization is created, represented by the emergence of a new subject of law. The will to be a partner is nothing more than the will that any party has when entering into any contract. Second, because the authorization for dissolution, especially when exercising the right of withdrawal in partnerships contracted for an indefinite period, corresponds to the recognition that, at least in commercial law, eternal contracts are not allowed. The affectio societatis, therefore, is overcome